2018
DOI: 10.1080/09593330.2018.1505960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline treatment on pathogens, bacterial community and antibiotic resistance genes in different sewage sludges for potential agriculture use

Abstract: Alkaline treatment is widely used to reduce pathogens in sewage sludge in developing countries and guarantee that it is safe for use in agriculture. The aim of this study was to investigate the effect of alkaline treatment applied to waste-activated (WAS) and Upflow Anaerobic Sludge Blanket (UASB)-sludge on the bacterial community, pathogens (viable helminths eggs and Salmonella spp), and antibiotic resistance genes (ARG). The bacterial community structure was examined through denaturing gel gradient electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…The problem is among other caused by some antibiotics (e.g. fluoroquinolones, cotrimoxazole, aminoglycosides), which are characterized with the highest activity in alkaline environments (Lopes et al 2020 ).…”
Section: Sludge Treatment Methodsmentioning
confidence: 99%
“…The problem is among other caused by some antibiotics (e.g. fluoroquinolones, cotrimoxazole, aminoglycosides), which are characterized with the highest activity in alkaline environments (Lopes et al 2020 ).…”
Section: Sludge Treatment Methodsmentioning
confidence: 99%
“…In addition, it denotes adequate hygienic procedures and quality/selection of the raw materials [18], starting with adequate purity of the water and the inorganic salts used for culture medium preparation and replenishment. Actually, although the strong alkaline conditions suitable for thriving of Arthrospira largely limit bacterial proliferation and viability of pathogens [93], the use of water sources not properly controlled and/or treated for good microbial quality during the cultivation process represents a potential concern in terms of product safety, as alkaliphilic pathogens can survive in the cultures and ultimately contaminate the biomass [15,18,23]. In parallel, several studies under laboratory conditions have revealed the negative or even lethal impact of high concentrations of Fe, Cu, Zn, Ni and Cd added in the culture media on A. platensis growth and cellular contents, and the fast accumulation of these metals in the biomass at concentrations up to one order of magnitude higher than the control, due to the high biosorption capacity of Arthrospira cells [94][95][96].…”
Section: Elementsmentioning
confidence: 99%
“…To sum up, the results demonstrated that while traditional treatment methods can effectively reduce toxicity, residual effects in wastewater may pose a risk to the ecosystem based on effect trigger values. Lopes et al (2020) [ 24 ] detected bacterial community structure by denatuated gel gradient electrophoresis (DGGE) and evaluated antibiotic resistance genes (ARG) by polymerase chain reaction (PCR). ARG has been detected in sludge samples after alkalization treatment, which may have an impact on human health.…”
Section: Literature Reviewmentioning
confidence: 99%